The Effect of Work Environment and Compesation on Employee Performance at PT. Premiumtrans Lintas Nusantara - Mumtaz, Hanifah Mutiarani; Purwanto, Sigit; Wibowo, Agung (INOVATOR, 2024)
The aim of this research is to determine the relationship between employee performance and pay and work environment. Personnel from all 31 PT Premiumtrans Lintas Nusantara were included in the study. This study used the Saturated Sampling Technique to choose a sample of 31 employees from the whole workforce. Primary data are used in this study. methods for gathering data that include surveys, questionnaire, and observation. Research of this kind is quantitative. The findings demonstrated that, with a significance value of 0.000 <0.05 and a t-count value of 4,384 > 2,048, the work environment variable (X1) had a positive and significant effect on the performance variable (Y). With a significance value of 0.130> 0.05 and a t-count of 1.561 < 2.048, the compensation variable (X2) has no discernible impact on performance (Y). Performance (Y) is significantly impacted by work environment (X1) and compensation (X2), with an f-count value of 23,723 > 3.34 and a significance value of 0.000 < 0.05.